An Optimization Model for Hospital Emergency Room Based on Patient Growth and Capacity Management - Widyasari, Rina; Cipta, Hendra; Nasution, Mutiah (Sinkron : jurnal dan penelitian teknik informatika, 2023)
According to government regulations of the Republic of Indonesia through the Ministry of Health, the hospital is a health service institution that organizes full individual health services that provide inpatient, outpatient and emergency services. The hospital can function as a place of final service by handling patients according to their abilities. Therefore, the facilities, infrastructure, and resources of the emergency room must be adequate so that they are able to cope with patients. In the case of COVID-19, the number of needs and capacities coupled with the need for demand forecasting and capacity management, especially in the emergency room at the Malahayati Hospital Medan is very necessary. So in this study, the mathematical model was built that could provide a solution to the problem of the need for demand forecasting and capacity management in the emergency room. The mathematical model for the exact outcome is determined by the relationship that exists between states and events. In this study, it is assumed that all events have a fixed probability, without considering drug administration and waiting time. For this reason, the method used the Support Vector Machine (SVM) which is expected to provide an estimate of how many people and capacity management needs are needed in the emergency room when the COVID-19 pandemic occurs. The mathematical model that was built was then simulated in the final part of this study using sample data taken from the Malahayati Hospital Medan.